The Effects of Trust, Commitment and Satisfaction on Customer Loyalty in the Distribution Sector - Bricci, L. (2017)
The main goal of this investigation is to demonstrate the main effects of trust, commitment and customer satisfaction on loyalty with a sample of customers from the distribution sector in Portugal. The results showed that trust has a positive and direct effect on commitment, also trust has a positive and direct effect on satisfaction, commitment has a positive and direct effect on loyalty and satisfaction has a positive and direct effect on loyalty, thus it´s important for this companies the improvement of responsibility, development of team skills, empowering employees and the company in a sense to fulfill commitments and performing the co-creation of value.